PENGARUH SUBSTITUSI TEPUNG IKAN DENGAN TEPUNG KEPALA IKAN PATIN (Pangasius sp) TERHADAP PERTUMBUHAN IKAN LELE SANGKURIANG (Clarias sp) - Yesica Manullang; Limin Santoso; Tarsim . (Universitas Sriwijaya, 2018)
ABSTRACTThe research was conducted at the Aquaculture Laboratory, University of Lampung in May to July, 2018. The aim of this study is to determine the effect of substitution of fish meal with catfish head flour on the growth of catfish, and head flour dosage the best for catfish growth. The study used a Completely Randomized Design with 3 treatments and 3 replications A (100% fish meal), B (70% fish meal and 30% catfish flour), and C (40% fish meal and 60% catfish flour). Parameters observed included absolute growth, daily growth rate, protein retention, feed convertion ratio (FCR), survival rate (SR), and supporting parameters that is feed cost and water quality. The data obtained were analyzed by variance and continued with smallest real difference test with a 95% confidence level. The results showed that the proportion of catfish head flour in artificial feed had an effect on absolute weight growth and daily growth rate (P, 0.001). The proportion of the use of 30% starch in the feed of catfish has a real influence on absolute growth (40.25 ± 5.67 g), and daily growth rate (0.67 ± 0.09 g/day).Keywords : Catfish, catfish head waste, substitution, feed, growth